The Influence Of Discipline, Motivation, And Work Environment On Employee Performance At West Java High Prosecutor's Office - Ramses Pardamean Siahaan; Mariana Rachmawati (Dinasti International Journal of Education Management And Social Science, 2025)
Employee performance basically has a big influence on the success of a company, good employee performance will also be a good result for the company's development. A company is said to be developing if there is good performance in the company. There are many factors that can influence an employee's performance. However, in this research, the author focuses on determining the influence of discipline, motivation, and work environment on employee performance. The method used in this research is a quantitative method with a descriptive research approach and verification analysis. The primary data collection technique was carried out through distributing questionnaires to all employees West Java High Prosecutor’s Office. The research results show that employee responses regarding discipline and the work environment are in the high category. Furthermore, employee responses regarding the work environment and performance are included in the very high category. The research results identified that partially disciplined employees contributes positively and significantly to employee performance . Partially the motivation of employees contributes negatively and significantly to employee performance . Partially the work environment of employees contributes positively and significantly to employee performance.